The Management of Scabies in the 21st Century: Past, Advances and Potentials - Charlotte Bernigaud; Katja Fischer; Olivier Chosidow (Medical Journals Sweden, 2020)
Scabies is one of the most common skin diseases worldwide, affecting 150-200 million people yearly. Scabies affects young children in particular, and has the greatest impact in poor overcrowded living conditions. The burden of the disease is now well characterized, including group A Streptococcus and Staphylococcus aureus bacterial superinfections, with reports of nephritis, acute rheumatic fever, or fatal invasive sepsis secondary to scabies. Management of scabies remains largely suboptimal from diagnosis to treatment, and progress in the development of new therapeutic measures leading to cure is urgently needed. This review gives an overview of the current limitations in the management of scabies, an update on recent advances, and outlines prospects for potential improvements.